Association Between Red Blood Cell Distribution Width and Prognosis of Renal Transplant Recipients with Early-Onset Pneumonia - Ming, Yingzi; Yang, Min; Peng, Bo; Zhuang, Quan; Stefano, George B; Kream, Richard M; Liu, Hong (Medical Science Monitor, 2019)
BACKGROUND Following renal transplantation, early-onset pneumonia is a frequent and severe infection-related complication. Red blood cell distribution width (RDW) has been reported as a predictive marker among patients with infectious diseases. Therefore, the aim of this study was to explore the significance of RDW in predicting prognosis, including 60-day mortality, in renal transplant recipients with early-onset pneumonia. MATERIAL AND METHODS Clinical data from patients who developed early-onset pneumonia after renal transplantation were retrospectively reviewed. Patients were divided into 2 groups: those with an RDW ≤15.0% and those with an RDW >15.0%. The 60-day mortality, bacteremia, need for mechanical ventilation, renal transplant rejection rate, and number of admissions to the intensive care unit (ICU) were estimated by Kaplan-Meier methods. Univariate and multivariate Cox regression analyses were performed to determine the risk factors for 60-day mortality. RESULTS Among the 118 patients participating in the study, 18 (15.2%) died during the 60-day follow-up. Kaplan-Meier analysis showed a death rate of 9.38% in the group with an RDW ≤15.0%, and a death rate of 40.9% in the group with an RDW >15.0% (P<0.001). Patient prognosis, including episodes of mechanical ventilation, graft rejection, and ICU admissions were significantly different between groups (P<0.01). RDW was an independent factor related to higher 60-day mortality (HR, 1.672; 95% CI, 1.111-2.516). CONCLUSIONS Among patients with early-onset pneumonia following renal transplantation, increased RDW >15.0% was significantly associated with prognosis and 60-day mortality.
Keywords: Pneumonia; Kidney Transplantation; Prognosis; lidé středního věku; erytrocytární znaky; proporcionální rizikové modely; Female; Humans; dospělí; Kaplanův-Meierův odhad; Male; Erythrocyte Indices; ženské pohlaví; Middle Aged; prognóza; lidé; pneumonie; Transplant Recipients; mužské pohlaví; příjemce transplantátu; Kaplan-Meier Estimate; Adult; Proportional Hazards Models; transplantace ledvin